Correction: Rapid access to diverse, trifluoromethyl-substituted alkenes using complementary strategies. Issue 22 (25th May 2018) - Phelan, James P.; Wiles, Rebecca J.; Lang, Simon B.; Kelly, Christopher B.; Molander, Gary A.
Abstract : Correction for 'Rapid access to diverse, trifluoromethyl-substituted alkenes using complementary strategies' by James P. Phelan et al., Chem. Sci., 2018, 9, 3215–3220.